The hydrothermal synthesis of BiOBr flakes for visible-light-responsive photocatalytic degradation of methyl orange - Jiang, Z; Yang, F; Yang, G; Kong, L; Jones, M; Xiao, T; Edwards, P (2010)
Flake-like BiOBr semiconductors have been prepared using hydrothermal synthesis with meticulous control of synthesis parameters and used for photocatalytic degradation of methyl orange. XRD, SEM and UV-vis characterizations have been performed to study the obtained BiOBr materials. The results indicate that the morphology and crystallite size of BiOBr depend significantly on the temperature and duration of the hydrothermal syntheses. Diffuse UV-vis spectra show the BiOBr materials to be indirect semiconductors with an optical bandgap of approximately 2.92 eV, which is essentially unaffected by the synthesis parameters. The hydrothermal-synthesized BiOBr flakes exhibit noticeable activity for photo-degradation of methyl orange under visible light (>400 nm) illumination, with the BiOBr synthesized by hydrothermal treatment at 120 °C for 6 h exhibiting superior photocatalytic performance in these flakes. The excellent activity and photo-stability reveal that BiOBr is a promising visible-light-responsive photocatalyst. © 2010 Elsevier B.V. All rights reserved.